A solid-state battery cell and preparation method thereof, and a solid-state lithium-ion battery

By introducing specific sulfide electrolytes into the cell of solid-state lithium-ion batteries, the interface compatibility and lithium ion transmission rate of the positive electrode layer and the electrolyte layer are improved, and the problem of poor battery circulation performance and capacity retention is solved, and higher energy density and safety are achieved.

CN116315055BActive Publication Date: 2025-04-22NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310454026.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-23
Publication Date
2025-04-22
Estimated Expiration
2043-04-23

AI Technical Summary

Technical Problem

During the circulation process of solid-state lithium-ion batteries, the interface contact becomes worse due to the expansion of the particle volume of the positive electrode active material, and the battery circulation performance and capacity retention rate are poor.

Method used

By introducing the first sulfide electrolyte and the second sulfide electrolyte into the solid battery cell, the interface compatibility between the positive electrode layer and the solid electrolyte layer is improved, and the transmission rate of lithium ions is improved.

Benefits of technology

It significantly improves the cycling performance and capacity retention rate of solid-state lithium-ion batteries, reduces interface impedance, and enhances the energy density and safety of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116315055B_ABST
    Figure CN116315055B_ABST
Patent Text Reader

Abstract

The present invention provides a solid-state battery cell and a preparation method thereof and a solid-state lithium-ion battery. The solid-state battery cell comprises a stacked positive electrode layer and a solid electrolyte layer; the solid electrolyte layer comprises a first sulfide electrolyte; the positive electrode layer comprises a positive electrode active material and a second sulfide electrolyte; the molecular formula of the first sulfide electrolyte is Li a1 M b1 PS c1 X d1 , the molecular formula of the second sulfide electrolyte is Li a2 M b2 PS c2 X d2 , wherein b1:b2 is 1:1 to 1:2, wherein X is selected from halogen, and M is selected from at least one of Na and K. The battery cell can improve the cycle performance and capacity retention rate of the solid-state lithium-ion battery by improving the interface compatibility between the positive electrode layer and the solid electrolyte layer and increasing the transmission rate of lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid-state batteries, and in particular relates to a solid-state battery cell and a preparation method thereof, and a solid-state lithium-ion battery. Background Art

[0002] Solid-state lithium battery is a lithium-ion battery that uses solid electrolyte instead of liquid electrolyte. Due to the fixity of solid electrolyte, solid-state lithium battery has the advantages of high energy density and high safety and is widely used in new energy vehicles and other fields. The interface contact between the electrolyte layer and the positive electrode layer directly affects the overall performance of the solid-state lithium battery. During the battery cycle, due to the volume expansion of the positive electrode active material particles during the charging and discharging process, the interface contact deteriorates and the battery cycle performance deteriorates. At present, the main means to improve the interface contact between the positive electrode layer and the electrolyte layer is to apply external pressure to the positive electrode layer, such as cold pressing, hot pressing, rolling, etc. However, since the positive electrode layer and the electrolyte layer use different materials, there is still a large potential difference between the two, which increases the interface impedance, and ultimately leads to poor cycle performance and low capacity retention of solid-state lithium batteries. Summary of the invention

[0003] The present invention provides a solid-state battery core, which improves the cycle performance and capacity retention rate of a solid-state lithium-ion battery by improving the interface compatibility between a positive electrode layer and a solid electrolyte layer and increasing the transmission rate of lithium ions.

[0004] The present invention provides a method for preparing a solid-state battery cell, which can be used to prepare the solid-state battery cell and has the advantages of simple preparation method, low cost, etc.

[0005] The present invention provides a solid-state lithium-ion battery. As the battery comprises the solid-state battery core, the battery has excellent performance in terms of cycle performance and capacity retention rate.

[0006] A first aspect of the present invention provides a solid-state battery cell, comprising a positive electrode layer and a solid electrolyte layer stacked in layers;

[0007] The solid electrolyte layer comprises a first sulfide electrolyte; the positive electrode layer comprises a positive electrode active material and a second sulfide electrolyte;

[0008] The molecular formula of the first sulfide electrolyte is Li a1 M b1 PS c1 X d1 , the molecular formula of the second sulfide electrolyte is Li a2 M b2 PS c2 X d2 , wherein b1:b2 is 1:1 to 1:2, X is selected from halogen, and M is selected from at least one of Na and K.

[0009] The solid-state battery cell as described above, wherein a1 is 5.5 to 6.5, b1 is 0.001 to 0.1, c1 is 4.5 to 5.5, and d1 is 0.9 to 1.6; and / or,

[0010] a2 is 5.5~6.5, b2 is 0.001~0.1, c2 is 4.5~5.5, and d2 is 0.9~1.6.

[0011] In the solid-state battery cell as described above, the mass ratio of the sum of the mass of the positive electrode active material and the second sulfide electrolyte to the mass of the first sulfide electrolyte is (1-6):30.

[0012] The solid-state battery cell as described above, wherein, in the positive electrode layer, the mass ratio of the positive electrode active material to the second sulfide electrolyte is (6:4) to (9.5:0.5).

[0013] The solid-state battery cell as described above, wherein the molecular formula of the positive electrode active material is Li x Na y Ni e Co f Mn g O z ,

[0014] Among them, e+f+g=1, 0.1≤e<0.5, 0≤f≤0.3, 0.5≤g<0.9; 1<x+y≤1.5, 1≤x<1.5, 0<y≤0.5; 2≤z≤2.5.

[0015] The solid-state battery cell as described above, further comprises a negative electrode layer, wherein the positive electrode layer, the solid electrolyte layer and the negative electrode layer are stacked in sequence.

[0016] In the solid-state battery cell as described above, the material of the negative electrode layer includes indium or lithium-indium alloy.

[0017] A second aspect of the present invention provides a method for preparing the solid-state battery cell as described above, comprising the following steps:

[0018] A solid electrolyte layer is obtained by pressing a raw material including at least a first sulfide electrolyte;

[0019] Placing a raw material including at least a positive electrode active material and a second sulfide electrolyte on one side of the solid electrolyte layer to obtain an intermediate;

[0020] The intermediate is subjected to compression molding to obtain the solid-state battery cell.

[0021] The preparation method as described above, wherein the step of placing the material of the negative electrode layer on the other side of the solid electrolyte layer is further included before the compression molding process.

[0022] The preparation method as described above, wherein the first sulfide electrolyte and the second sulfide electrolyte are each independently prepared by a method comprising the following processes: sintering a raw material comprising lithium sulfide, phosphorus sulfide, a halogen compound and an alkali metal compound;

[0023] Wherein, the alkali metal compound is selected from Na compounds and / or K compounds; the sintering treatment temperature is 510° C. to 560° C., and the sintering time is 3 to 8 hours.

[0024] A third aspect of the present invention provides a solid-state lithium-ion battery, comprising the solid-state battery cell as described above.

[0025] The implementation of the present invention has at least the following beneficial effects:

[0026] In the solid-state battery cell of the present invention, the lithium ion transmission rate of the first sulfide electrolyte and the second sulfide electrolyte is greater than that of the positive electrode active material. The introduction of the first sulfide electrolyte and the second sulfide electrolyte is conducive to improving the transmission rate of lithium ions. At the same time, the first sulfide electrolyte and the second sulfide electrolyte have the same elemental composition, which is conducive to improving the interface compatibility between the positive electrode layer and the solid electrolyte layer. It can be seen that the present invention improves the cycle performance and capacity retention rate of the solid-state lithium ion battery by improving the interface compatibility between the positive electrode layer and the solid electrolyte layer and increasing the transmission rate of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a SEM image of the sulfide electrolyte of Example 1 of the present invention at the first magnification;

[0028] Figure 2 This is a SEM image of the sulfide electrolyte of Example 1 of the present invention at the second magnification. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In a first aspect of the present invention, a solid-state battery cell is provided, comprising a stacked positive electrode layer and a solid electrolyte layer; the solid electrolyte layer comprises a first sulfide electrolyte; the positive electrode layer comprises a positive electrode active material and a second sulfide electrolyte; the molecular formula of the first sulfide electrolyte is Li a1 M b1PS c1 X d1 The molecular formula of the second sulfide electrolyte is Li a2 M b2 PS c2 X d2 , wherein b1:b2 is 1:1 to 1:2, X is selected from halogen, and M is selected from at least one of Na and K.

[0031] The solid-state battery cell of the present invention comprises a positive electrode layer and a solid electrolyte layer. The positive electrode layer is used to provide active material, such as a lithium-containing compound. The solid electrolyte layer can conduct lithium ions, especially when the solid-state battery cell is used as a battery unit, the solid electrolyte layer can conduct lithium ions between the positive electrode layer and the negative electrode layer.

[0032] The present invention does not limit the arrangement of the positive electrode layer, as long as the positive electrode layer and the solid electrolyte layer are stacked. For example, the positive electrode layer can be stacked alone on one side of the solid electrolyte layer, or it can be bonded to one side of the solid electrolyte layer. In this case, the positive electrode layer of the present invention has an interface in contact with the solid electrolyte layer.

[0033] The solid electrolyte layer comprises a first sulfide electrolyte, and the positive electrode layer comprises a positive electrode active material and a second sulfide electrolyte, wherein the molecular formula of the first sulfide electrolyte is Li a1 M b1 PS c1 X d1 The molecular formula of the second sulfide electrolyte is Li a2 M b2 PS c2 X d2 The first sulfide electrolyte and the second sulfide electrolyte have the same elemental composition. Since the positive electrode layer and the solid electrolyte layer contain sulfide electrolytes with the same elemental composition, the positive electrode layer and the solid electrolyte layer have good interface compatibility.

[0034] Wherein, M is selected from at least one of Na and K, and X is selected from halogen, such as fluorine (F), chlorine (Cl), bromine (Br), iodine (I), etc. b1:b2 is 1:1 to 1:2, such as 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or a range consisting of any two of them.

[0035] According to the molecular formula of the first sulfide electrolyte and the second sulfide electrolyte, compared with the conventional sulfide electrolyte containing only Li, P, S, and X, the first sulfide electrolyte and the second sulfide electrolyte of the present invention use Na and K to replace part of the Li sites in the conventional sulfide electrolyte. + , K+ The ion radius of Li is larger than that of Li, which reduces the tortuosity of lithium ion transmission and increases the path of lithium ion transmission, thereby increasing the lithium ion transmission rate. Among them, the higher the sodium and potassium content, the higher the lithium ion transmission rate.

[0036] In addition to the positive electrode active material in the positive electrode layer being used to provide active materials, the second sulfide electrolyte can utilize the remaining Li sites as the active material to release capacity. At this time, the positive electrode active material and the second sulfide electrolyte jointly provide the active material to release capacity. In addition, the second sulfide electrolyte can also effectively conduct lithium ions. At this time, the second sulfide electrolyte and the first sulfide electrolyte can jointly improve the transmission rate of lithium ions. It can be seen that the solid-state battery cell of the above structure can not only ensure that the positive electrode layer and the solid electrolyte layer have good interface compatibility, but also enable lithium ions to be smoothly embedded and de-embedded in the positive electrode layer, thereby improving the transmission rate of lithium ions.

[0037] Furthermore, when 1:1<b1:b2≤1:2 is satisfied, the M content of the second sulfide electrolyte is greater than the M content of the first sulfide electrolyte, which is beneficial to further improve the lithium ion transfer rate of the positive electrode layer, so that the lithium ion transfer rates of the positive electrode layer and the solid electrolyte layer are adapted, thereby further improving the cycle performance and capacity retention rate of the battery.

[0038] According to the research of the present invention, the above-mentioned solid-state battery cell is applied to a solid-state lithium-ion battery, and the solid-state lithium-ion battery performs well in terms of cycle performance and capacity retention. This is because, on the one hand, the positive electrode layer and the solid electrolyte layer respectively contain sulfide electrolytes of the same elemental composition, so that the positive electrode layer and the solid electrolyte layer have good interface compatibility, which greatly reduces the interface impedance of the positive electrode layer and the solid electrolyte layer, thereby facilitating the improvement of the cycle performance and capacity retention of the solid-state lithium-ion battery; on the other hand, the first sulfide electrolyte and the second sulfide electrolyte of the present invention use Na and K to replace part of the Li sites in the conventional sulfide electrolyte, so that the first sulfide electrolyte and the second sulfide electrolyte have higher ionic conductivity, due to Na + , K + The ionic radius of Li is larger than that of Li, which reduces the tortuosity of lithium ion transmission, increases the path of lithium ion transmission, and thus improves the transmission rate of lithium ions, avoiding the problem of poor interface contact caused by volume expansion of the positive electrode layer during the cycle. In addition, the second sulfide electrolyte can also release capacity as an active material. It can be seen that the solid-state battery provided by the present invention can improve the cycle performance and capacity retention rate of solid-state lithium-ion batteries by improving the interface compatibility between the positive electrode layer and the solid electrolyte layer, improving the ionic conductivity of the sulfide electrolyte, improving the transmission rate of lithium ions, and improving the capacity.

[0039] In one embodiment, a1 is 5.5 to 6.5, b1 is 0.001 to 0.1, c1 is 4.5 to 5.5, and d1 is 0.9 to 1.6; and / or, a2 is 5.5 to 6.5, b2 is 0.001 to 0.1, c2 is 4.5 to 5.5, and d2 is 0.9 to 1.6. By limiting the element content in the first sulfide electrolyte and the second sulfide electrolyte, it is beneficial to improve the structural stability of the first sulfide electrolyte and the second sulfide electrolyte, thereby further improving the interface compatibility between the positive electrode layer and the solid electrolyte layer and the lithium ion transfer rate.

[0040] By rationally adjusting the mass ratio of the active ingredients in the positive electrode layer and the solid electrolyte layer, it is beneficial to further improve the cycle performance and capacity retention rate of the solid-state lithium-ion battery. In some embodiments, the mass ratio of the sum of the mass of the positive electrode active material and the second sulfide electrolyte to the mass of the first sulfide electrolyte is (1 to 6):30. When the solid electrolyte layer only contains the first sulfide electrolyte and the positive electrode layer only contains the positive electrode active material and the second sulfide electrolyte, the mass ratio of the positive electrode layer to the solid electrolyte layer is (1 to 6):30, for example, 1:30, 2:30, 3:30, 4:30, 5:30, 6:30 or a range consisting of any two of them.

[0041] The present invention does not limit the mass ratio of the positive electrode active material to the second sulfide electrolyte in the positive electrode layer, as long as the positive electrode layer contains the positive electrode active material and the second sulfide electrolyte. By adjusting the positive electrode active material and the second sulfide electrolyte, it is beneficial to further improve the capacity and lithium ion transmission rate. In some embodiments, in the positive electrode layer, the mass ratio of the positive electrode active material to the second sulfide electrolyte is (6:4) to (9.5:0.5), for example, 6:4, 7:3, 8:2, 9:1, 9.5:0.5 or a range composed of any two of them.

[0042] The present invention does not limit the specific molecular formula of the positive electrode active material, and it can be a conventional positive electrode active material in the art. In some embodiments, the molecular formula of the positive electrode active material is Li x Na y Ni e Co f Mn g O z ,

[0043] Among them, e+f+g=1, 0.1≤e<0.5, 0≤f≤0.3, 0.5≤g<0.9; 1<x+y≤1.5, 1≤x<1.5, 0<y≤0.5; 2≤z≤2.5. The inventor believes that the positive electrode active material with this molecular formula, used in combination with the above-mentioned second sulfide electrolyte, can further improve the capacity and cycle performance of the battery.

[0044] The solid-state battery cell of the present invention also includes a negative electrode layer, a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are stacked in sequence. At this time, the solid electrolyte layer has two opposite sides in the stacking direction, the positive electrode layer is located on one side of the solid electrolyte layer, and the solid electrolyte layer is located on the other side of the solid electrolyte layer. The present invention does not limit the arrangement of the negative electrode layer, as long as the positive electrode layer, the solid electrolyte layer, and the negative electrode layer are stacked in sequence. For example, the negative electrode layer can be stacked alone on the other side of the solid electrolyte layer, or it can be bonded to the other side of the solid electrolyte layer.

[0045] The present invention does not limit the specific material of the negative electrode layer. For example, in some embodiments, the material of the negative electrode layer includes indium or lithium-indium alloy. These negative electrode layer materials have higher lithium storage capacity than traditional graphite negative electrodes, so the use in solid-state lithium-ion batteries can achieve higher energy density.

[0046] The negative electrode layer may be composed of a single indium foil or a stack of lithium foil and indium foil. When the negative electrode layer is composed of a stack of lithium foil and indium foil, the indium foil is attached to the other side of the solid electrolyte layer, and the lithium foil is located on the side of the indium foil away from the solid electrolyte layer.

[0047] The solid-state battery cell of the present invention may further include a negative electrode current collector, which is located on the surface of the negative electrode layer away from the solid electrolyte layer, and the negative electrode current collector plays a role in supporting the negative electrode layer. In this way, while ensuring the electrochemical performance of the solid-state lithium-ion battery, it also helps to improve the structural stability of the battery. Among them, the negative electrode current collector can be copper foil or the like.

[0048] The present invention does not limit the thickness of the positive electrode layer, the solid electrolyte layer, and the negative electrode layer in the solid-state battery cell, and the thickness can be adjusted according to actual needs.

[0049] The present invention also includes a tab, which is used to connect to an external circuit. Specifically, a negative tab can be led out on one side of the negative electrode layer, and a positive tab can be led out on one side of the positive electrode layer.

[0050] A second aspect of the present invention provides a method for preparing the solid-state battery cell provided in the first aspect, comprising the following steps:

[0051] A solid electrolyte layer is obtained by pressing a raw material including at least a first sulfide electrolyte;

[0052] Placing a raw material including at least a positive electrode active material and a second sulfide electrolyte on one side of the solid electrolyte layer to obtain an intermediate;

[0053] The intermediate is subjected to compression molding to obtain a solid-state battery cell.

[0054] The present invention does not impose too many restrictions on the specific process of the above-mentioned pressing treatment and pressing molding treatment, as long as the above-mentioned raw materials can form a stacked positive electrode layer and a solid electrolyte layer after the pressing treatment and pressing molding treatment.

[0055] The pressing and molding process also includes the following steps: placing the material of the negative electrode layer on the other side of the solid electrolyte layer. At this time, at least the raw materials including the positive electrode active material and the second sulfide electrolyte are located on one side of the solid electrolyte layer. The above materials are pressed as an integrated whole to obtain a solid-state battery cell, so that in the solid-state battery cell, the positive electrode layer, the solid electrolyte layer, and the negative electrode layer are stacked in sequence.

[0056] The present invention does not place too many restrictions on the specific material of the above-mentioned negative electrode layer. In one embodiment, the indium foil is placed close to the other side of the solid electrolyte layer, the lithium foil is placed on the side of the indium foil away from the solid electrolyte layer, and the negative electrode current collector is placed on the side of the lithium foil away from the solid electrolyte layer, and then an integrated press forming process is performed. At this time, the negative electrode layer includes stacked lithium foil and indium foil, and the positive electrode layer, solid electrolyte layer, negative electrode layer, and negative electrode current collector are stacked in sequence.

[0057] The present invention does not limit the preparation process of the first sulfide electrolyte and the second sulfide electrolyte, and conventional doping methods in the art can be used. For example, compounds containing the above elements can be mixed as raw materials and directly added for synthesis, or conventional sulfide electrolytes can be synthesized and then doped or coated. In some embodiments, the first sulfide electrolyte and the second sulfide electrolyte are each independently prepared by a method comprising the following processes: sintering raw materials including lithium sulfide, phosphorus sulfide, halogen compounds and alkali metal compounds, wherein the alkali metal compounds are selected from Na compounds and / or K compounds; the sintering treatment temperature is 510°C to 560°C, and the time is 3 to 8 hours. The preferred sintering temperature is 530°C and the time is 6 hours.

[0058] The third aspect of the present invention provides a solid-state lithium-ion battery, comprising the solid-state battery cell of the first aspect or the solid-state battery cell prepared by the preparation method provided by the second aspect. The solid-state battery cell of the present invention can be directly used as a solid-state lithium-ion battery after assembly, and the quality of the solid-state battery cell directly determines the quality of the solid-state lithium-ion battery. Since the battery of the present invention adopts the above-mentioned solid-state battery cell, the solid-state lithium-ion battery performs well in terms of cycle performance and capacity retention rate.

[0059] The present invention will be further described below by means of specific examples.

[0060] Example 1

[0061] Na2S, Li2S, P2S5, and LiCl were mixed by high-energy ball milling in a molar ratio of 0.1:4.9:1:2 to obtain a mixture; wherein the ball milling speed was 450r, the ball milling time was 6h, and the mixture was sintered in an argon atmosphere, and the sulfide electrolyte Li was obtained after crushing. 5.9 Na 0.1 PS5Cl, the sulfide electrolyte is used as the first sulfide electrolyte and the second sulfide electrolyte; wherein the sintering temperature is 530°C, the time is 6h, and the heating rate is 5°C / min;

[0062] 0.15g of the first sulfide electrolyte was cold pressed in a battery mold to obtain a solid electrolyte layer; 0.01g of the positive electrode layer material was placed on one side of the electrolyte layer (the positive electrode layer material included positive electrode active material and second sulfide electrolyte, with a mass ratio of 8:2), and the simple formula of the positive electrode active material was Li 1.2 Na 0.05 Ni 0.325 Co 0.1 Mn 0.575 O 2.25 ;

[0063] Place the indium foil close to the other side of the solid electrolyte layer, place the lithium foil on the side of the indium foil away from the solid electrolyte layer, place the negative electrode current collector on the side of the lithium foil away from the solid electrolyte layer, and then perform an integrated press molding process with a pressure holding time of ≥20 minutes to obtain a solid-state battery cell.

[0064] Example 2

[0065] The preparation method is basically the same as that in Example 1, except that the first sulfide electrolyte is different. The first sulfide electrolyte in this embodiment is prepared by the following method: Na2S, Li2S, P2S5, and LiCl are mixed by high-energy ball milling in a molar ratio of 0.05:4.95:1:2 to obtain a mixture; wherein the ball milling speed is 450r, the ball milling time is 6h, and the mixture is intermittently ball milled to sinter the mixture in an argon atmosphere, and the sulfide electrolyte Li is obtained after crushing. 5.95 Na 0.05 PS5Cl, the sulfide electrolyte is used as the first sulfide electrolyte and the second sulfide electrolyte; wherein the sintering temperature is 535°C, the time is 6h, and the heating rate is 5°C / min;

[0066] The sulfide electrolyte of this embodiment is used as the first sulfide electrolyte, the sulfide electrolyte of Example 1 is used as the second sulfide electrolyte, and other conditions remain unchanged to prepare a solid-state battery cell.

[0067] Example 3

[0068] The preparation method is basically the same as that in Example 1, except that the following sulfide electrolyte is used as the first sulfide electrolyte and the second sulfide electrolyte. The specific preparation method of the sulfide electrolyte in this embodiment is as follows: K2S, Li2S, P2S5, and LiCl are subjected to high-energy ball milling mixing treatment in a molar ratio of 0.03:4.97:1:2 to obtain a mixture; wherein the ball milling speed is 450r, the ball milling time is 6h, and the mixture is intermittently ball milled to sinter the mixture in an argon atmosphere, and the sulfide electrolyte Li is obtained after crushing. 5.97 K 0.03 PS5Cl; wherein the sintering temperature is 525°C, the time is 6h, and the heating rate is 5°C / min;

[0069] The sulfide electrolyte of this example is used as the first electrolyte and the second electrolyte, and other conditions remain unchanged to prepare a solid-state battery cell.

[0070] Example 4

[0071] The preparation methods of this embodiment are basically the same as those of embodiment 2, except that in the positive electrode layer, the mass ratio of the positive electrode active material to the second sulfide electrolyte is 9:1; other conditions remain unchanged, and a solid-state battery cell is obtained.

[0072] Example 5

[0073] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the negative electrode material of this embodiment is only indium foil, and other conditions remain unchanged to obtain a solid-state battery cell.

[0074] Example 6

[0075] The electrolyte obtained in Example 1 is used as the second sulfide electrolyte; the electrolyte obtained in Example 2 is used as the first sulfide electrolyte, and in this example, b1:b2=1:2; other conditions remain unchanged to prepare a solid-state battery cell.

[0076] Example 7

[0077] The preparation method is basically the same as that in Example 2, except that the second sulfide electrolyte is different. The second sulfide electrolyte in this example is prepared by the following method: Na2S, Li2S, P2S5, and LiCl are mixed by high-energy ball milling at a molar ratio of 0.075:4.925:1:2 to obtain a mixture; wherein the ball milling speed is 450r, the ball milling time is 6h, and the mixture is intermittently ball milled to sinter the mixture in an argon atmosphere, and the sulfide electrolyte Li is obtained after crushing. 5.925 Na 0.075 PS5Cl; wherein the sintering temperature is 525°C, the time is 6h, and the heating rate is 5°C / min;

[0078] The sulfide electrolyte of this embodiment is used as the second sulfide electrolyte, the sulfide electrolyte of embodiment 2 is used as the first sulfide electrolyte, and other conditions remain unchanged to prepare a solid-state battery cell.

[0079] Comparative Example 1

[0080] Li2S, P2S5, and LiCl are mixed by high-energy ball milling in a molar ratio of 5:1:2 to obtain a mixture; wherein the ball milling speed is 450r, the ball milling time is 6h, and the ball milling is intermittent; the mixture is sintered in an argon atmosphere, and a sulfide electrolyte is obtained after crushing, and the sulfide electrolyte is used as the first sulfide electrolyte and the second sulfide electrolyte of this embodiment; wherein the sintering temperature is 530°C, the time is 6h, and the heating rate is 5°C / min;

[0081] 0.15 g of the first sulfide electrolyte is cold-pressed in a battery mold to obtain a solid electrolyte layer;

[0082] 0.01 g of positive electrode layer material is placed on one side of the electrolyte layer (the positive electrode layer material includes positive electrode active material and second sulfide electrolyte, with a mass ratio of 8:2). The simple formula of the positive electrode active material is Li 1.2 Na 0.05 Ni 0.325 Co 0.1 Mn 0.575 O 2.25 ; Place the indium foil close to the other side of the solid electrolyte layer, place the lithium foil on the side of the indium foil away from the solid electrolyte layer, place the negative electrode current collector on the side of the lithium foil away from the solid electrolyte layer, and then perform an integrated press molding process with a pressure holding time of ≥20 minutes to obtain a solid-state battery cell.

[0083] Test example

[0084] The above method was repeated twice to obtain a solid-state battery cell, and the solid-state battery cell was assembled into a solid-state lithium-ion battery. The battery was subjected to a 0.05C first charge and discharge test, a 0.2C discharge test, and a 0.5C cycle performance test. The test results are shown in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] In Table 1, first effect = first discharge capacity / first charge capacity

[0089] Figure 1 and Figure 2It is a SEM image of the sulfide electrolyte of the embodiment of the present invention. According to Table 1, the solid-state battery cells provided in Examples 1-7 of the present invention are applied to the battery, and have excellent 0.2C discharge capacity and capacity retention rate relative to the comparative example, indicating that the battery of the embodiment has excellent cycle performance and capacity retention rate. In addition, the batteries of Examples 1-3 of the present invention have higher first efficiency, 0.2C discharge capacity and capacity retention rate relative to the comparative example. After research, the inventor believes that the positive electrode layer and the solid electrolyte layer respectively contain sulfide electrolytes with the same elemental composition, which is beneficial to improve the interface compatibility between the positive electrode layer and the solid electrolyte layer; and the first sulfide electrolyte and the second sulfide electrolyte use Na and K to replace part of the Li sites in the conventional sulfide electrolyte, which is beneficial to improve the transmission rate of lithium ions. According to Examples 1-7, by regulating the content of the M element, it is beneficial to further improve the cycle performance and capacity retention rate of the battery.

[0090] Example 4 has excellent first charge and discharge capacity, first efficiency, and 0.2C discharge capacity compared to Comparative Example 1, but the capacity retention rate is slightly reduced. The inventor believes that this may be because as the mass ratio of the positive electrode active material and the second sulfide electrolyte increases, the current density of the battery is small under low rate conditions, and the positive electrode layer is in good contact with the electrolyte layer, but as the current density increases, some capacity loss will occur. Example 5 has higher first discharge capacity, 0.2C discharge capacity and capacity retention rate compared to Comparative Example 1, but the first discharge efficiency is slightly lower. The inventor believes that this may be because when the negative electrode uses only indium foil, relative to the negative electrode prepared by using indium foil and lithium foil, some lithium is lost, resulting in a decrease in the first efficiency.

[0091] It should be noted here that the numerical values ​​and numerical ranges involved in the embodiments of the present invention are approximate values. Due to the influence of the manufacturing process, there may be a certain range of errors, which can be considered negligible by those skilled in the art.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

[0093] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A solid-state battery cell, characterized in that: It includes a positive electrode layer and a solid electrolyte layer which are stacked; The solid electrolyte layer comprises a first sulfide electrolyte; the positive electrode layer comprises a positive electrode active material and a second sulfide electrolyte; The molecular formula of the first sulfide electrolyte is Li a1 M b1 PS c1 X d1 , the molecular formula of the second sulfide electrolyte is Li a2 M b2 PS c2 X d2 , wherein b1:b2 is 1:1~1:2, X is selected from halogen, and M is selected from at least one of Na and K; a1 is 5.5~6.5, b1 is 0.001~0.1, c1 is 4.5~5.5, d1 is 0.9~1.6; a2 is 5.5~6.5, b2 is 0.001~0.1, c2 is 4.5~5.5, and d2 is 0.9~1.

6.

2. The solid-state battery cell according to claim 1, characterized in that: The mass ratio of the sum of the masses of the positive electrode active material and the second sulfide electrolyte to the first sulfide electrolyte is (1-6):

30.

3. The solid-state battery cell according to claim 1, characterized in that: In the positive electrode layer, the mass ratio of the positive electrode active material to the second sulfide electrolyte is (6:4) to (9.5:0.5).

4. The solid-state battery cell according to claim 1, characterized in that: The molecular formula of the positive electrode active material is Li x Na y Ni e Co f Mn g O z , Among them, e+f+g=1, 0.1≤e<0.5, 0≤f≤0.3, 0.5≤g<0.9; 1<x+y≤1.5, 1≤x<1.5, 0<y≤0.5; 2≤z≤2.

5.

5. The solid-state battery cell according to any one of claims 1 to 4, characterized in that: It also includes a negative electrode layer, wherein the positive electrode layer, the solid electrolyte layer and the negative electrode layer are stacked in sequence.

6. The solid-state battery cell according to claim 5, characterized in that: The material of the negative electrode layer includes indium or lithium-indium alloy.

7. A method for preparing a solid-state battery cell according to any one of claims 1 to 6, characterized in that: The following steps are involved: A solid electrolyte layer is obtained by pressing a raw material including at least a first sulfide electrolyte; Placing a raw material including at least a positive electrode active material and a second sulfide electrolyte on one side of the solid electrolyte layer to obtain an intermediate; The intermediate is subjected to compression molding to obtain the solid-state battery cell.

8. The preparation method according to claim 7, characterized in that: The method further includes the following steps before the compression molding process: placing the material of the negative electrode layer on the other side of the solid electrolyte layer.

9. The preparation method according to claim 7, characterized in that: The first sulfide electrolyte and the second sulfide electrolyte are each independently prepared by a method comprising the following process: sintering a raw material comprising lithium sulfide, phosphorus sulfide, a halogen compound and an alkali metal compound; Wherein, the alkali metal compound is selected from Na compounds and / or K compounds; the sintering treatment temperature is 510° C. to 560° C., and the sintering time is 3 to 8 hours.

10. A solid-state lithium-ion battery, characterized in that: A solid-state battery cell comprising any one of claims 1 to 6.

Citation Information

Patent Citations

  • Chalcogenide composite cathode material, an all-solid-state lithium battery thereof and a preparation method thereof

    CN109256555A

  • Sulfide solid electrolyte material, battery, and producing method for sulfide solid electrolyte material

    US20160240886A1